Thixotropic properties of waxy potato starch depending on the degree of the granules pasting. (5th May 2016) - Krystyjan, Magdalena; Sikora, Marek; Adamczyk, Greta; Dobosz, Anna; Tomasik, Piotr; Berski, Wiktor; Łukasiewicz, Marcin; Izak, Piotr
Abstract : Highlights: Rheological instability of waxy potato starch (WPS) pastes was studied. Pasting temperature and concentration of WPS influenced rheological parameters of the resulted pastes. Not only the concentration and temperature but also the rate of shear influence the thixotropic behavior. Autoclaved pastes, independently on the concentration showed the phenomenon of antithixotropy. Samples pasted at 80 and 95 °C showed both thixotropic and antithixotropic behavior, with a predominance of the latter. Abstract: This paper presents the rheological instability (thixotropy/antithixotropy) of waxy potato starch (WPS) pastes depending on their concentration (1–5% w/w) and pasting temperature (80, 95 and autoclaved: 121 °C, at 0.1 MPa). The hysteresis loop, apparent viscosity at constant shear rate as well as the in-shear structural recovery tests with and without pre-shearing were applied. The pastes were also characterized by the granularity profile, molecular weight, polydispersity and optical transmittance. Differences in rheological properties of the pastes prepared at 80 and 95 °C as well as autoclaved resulted from degree of granules pasting. At 121  °C dissolution of the granules occurred, while at the lower temperatures only the partial pasting of the granules took place. Pasting temperature of WPS significantly influenced rheological parameters of the resulted pastes which had thixotropic, antithixotropic or mixed thixotropic/antithixotropic behavior. Autoclaved pastes, regardless their concentration were antithixotropic as demonstrated by the areas of hysteresis loops derived from the flow curves signalized by the degree of structure recovery (DSR) which exceeded unity. The apparent viscosity of WPS pasted at 121 °C strongly decreased as compared to the samples pasted at lower temperatures. Samples pasted at 80 and 95 °C showed both thixotropic and antithixotropic behavior, with a predominance of the latter. The starch concentration played an important role in the formation of the rheological properties of the resulted pastes. Its influence was strongly connected with the degree of the granules pasting, therefore with the temperature of pastes preparation. For the pastes prepared at 80 and 95 °C the values of thixotropy and apparent viscosity increased, while the values of DSR decreased with an increase of concentration. In the autoclaved pastes the antithixotropy, DSR and apparent viscosity increased with increasing starch concentration. It was also found that apart from the concentration and temperature also the shear rate influence the thixotropic behavior.